ANALISIS RETRIBUSI IZIN MENDIRIKAN BANGUNAN DALAM PERSPEKTIF HOLISTIK (Studi Pada Dinas Penataan Ruang dan Perumahan Kota Palu) - Arief, Mohamad; Ridwan, Ridwan; Yusnita, Nina (Katalogis, 2018)
The study aims to determine and analyze: 1) the cause of building permit retributions is not optimal in Palu City; 2) efforts taken in increasing building permit retributions; 3) contribution of building permit retributions to local retribution and local revenue in Palu City. The study applies qualitative approach with single holistic case study focusing on building permit retributions. The results find that: 1) the acceptance of building permit retributions is not optimal due to the lack of optimal supervision and control of buildings, manual data processing system, unsuitable human resources, and lack of awareness of the importance of having building permit; 2) efforts undertaken by the government of Palu to increase the acceptance of building permit retributions are done by reducing, facilitating, and relief obligation of building retributions known as ‘pemutihan IMB’, and socialization both direcly and through the mass media; 3) the contribution of building permit retribution to the local retribution averagely is in good criteria. While the contribution given by building permit to the local revenues is very low.